2014
DOI: 10.1590/0104-6632.20140314s00002997
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic capabilities of Actinobacillus succinogenes for succinic acid production

Abstract: -Attention has been focused on microbial succinic acid production as an alternative for conventional chemical synthesis that is associated with environmental pollution. A metabolic model for Actinobacillus succinogenes 130Z was developed with a mixture of glucose and xylose as substrate. The metabolic fluxes during succinicate production were determined using flux balance analysis by linear programming optimization in the MATLAB environment. Different glucose ratios (0.3, 0.4 and 0.7 mol.mol -1 substrate) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The post-genomic metabolic modeling studies are shown in Table 2. Rafieenia developed the metabolic model of A. succinogenes composed of 27 reactions and 28 metabolites with a sugar mixture of glucose and xylose by applying MFA via a computational technique [81]. Furthermore, constrained [88] and dynamic [90] MFA methods were employed to determine flux ranges and maximum productivity in A. succinogenes metabolism, respectively.…”
Section: Attempts At Metabolic Modeling Of a Succinogenesmentioning
confidence: 99%
“…The post-genomic metabolic modeling studies are shown in Table 2. Rafieenia developed the metabolic model of A. succinogenes composed of 27 reactions and 28 metabolites with a sugar mixture of glucose and xylose by applying MFA via a computational technique [81]. Furthermore, constrained [88] and dynamic [90] MFA methods were employed to determine flux ranges and maximum productivity in A. succinogenes metabolism, respectively.…”
Section: Attempts At Metabolic Modeling Of a Succinogenesmentioning
confidence: 99%
“…Nature of carbon source is a significant factor directly affecting metabolic fluxes, succinic acid yields and byproduct formation, as also influencing biotechnological process economics. Metabolic engineering produces industrial A. succinogenes strains, redirecting carbon flux towards succinate pathway instead of acetate and formate (Rafieenia, 2014). Mixed substrates, e.g.…”
Section: St Generation Biomassmentioning
confidence: 99%
“…Mixed substrates, e.g. xylose and glucose (Rafieenia, 2014), or fructose and glucose (Wang et al, 2011) for succinate, have often a positive influence on microbial production, basing on the principle of auxiliary carbon. Actinobacillus succinogenes overproduces succinic acid, from cheap feedstock glycerol using an external electron acceptor, e.g.…”
Section: St Generation Biomassmentioning
confidence: 99%
“…This model is intermediate in scale between a central carbon metabolism and a genome-scale metabolic model. While the model of Rafieenia [ 16 ] and other existing models proposed by McKinlay et al [ 3 , 4 , 6 , 8 ] focus on the central carbon metabolism, our model includes pathways for the major biomass components including amino acids, RNA, DNA, glycogen and lipids. Thus, our model can be termed as a comprehensive carbon metabolism model and not a genome scale model, since we do not explicitly include all the known metabolic pathways in A .…”
Section: Introductionmentioning
confidence: 99%